Pembelajaran Terintegrasi Berbasis Kecerdasan Majemuk Pada Anak Usia Dini - Layla Mardliyah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
Integrated learning based on multiple intelligences in early childhood is a learning activity that is oriented towards maximizing the growth and development process of early childhood through integrated and holistic activities. This study aims to describe Integrated Learning Activities Based on Multiple Intelligences in Early Childhood Education in Banyumas. This study uses a descriptive research method with a qualitative approach. Data was collected through observation, interviews and documents. The subjects of this study were school principals, teachers and students as well as parents' representatives. This research resulted in the following description: Integrated learning activities are carried out systematically through teacher activities based on planning aspects in the form of daily learning activity plans with reference to aspects of competence and child intelligence. Children's learning towards maximizing their potential is carried out by involving the role of parents in children's learning activities at home, by making daily activities and learning resources utilizing what is at home as learning material. Keywords: Integrated Learning, Multiple Intelligences, parents